The Maxim Violation on The Little Movie - Putra, I Gede Krismon Andika; Putu Devi Maharani; Putu Desi Anggerina Hikmaharyanti (Journal of Language and Applied Linguistics, 2025)
This study concerns the types of Maxim Violation related to the language that consist in the dialogue of the Little movie. This study used the theory of maxim violation which was proposed by Paul Grice (1975). The method used a qualitative method by following the data with the observation through watching and analyzing the dialogue in characters’ utterances and also reading the dialogue repeatedly and taking notes in the process of analyzing the data. The analysis found the character’s utterances violate maxim types mostly conducted by the main participants or the character in the movie, where the total of data is 32 times of maxim violation. The highest is 11 data or 34,38% violation maxim of quality, followed by 10 data or 31,25% of violation maxim of quantity, 6 data or 18,75% violation of maxim relevance and lastly 5 data or 15, 62% maxim violation of manner